My "A" Sound Box - Moncure, Jane Belk; Thornburgh, Rebecca McKillip (Mankato, MN : Child's World, 2009)
Little a has an adventure with items beginning with his letter's sound, such as apples, ants, and an astronaut.
Keywords: Alphabet